New Antibody Conjugates in Cancer Therapy - Serengulam V. Govindan; David M. Goldenberg (The Scientific World Journal)
Targeting of radiation, drugs, and protein toxins to cancers selectively with monoclonal antibodies (MAbs) has been a topic of considerable interest and an area of continued development. Radioimmunotherapy (RAIT) of lymphoma using directly labeled MAbs is of current interest after approval of two radiolabeled anti-CD20 MAbs, as illustrated with the near 100% overall response rate obtained in a recent clinical trial using an investigational radiolabeled anti-CD22 MAb, 90Y-epratuzumab. The advantage of pretargeted RAIT over directly labeled MAbs is continuing to be validated in preclinical models of lymphoma and solid tumors. Importantly, the advantages of combining RAIT with radiation sensitizers, with immunotherapy, or a drug conjugate targeting a different antigen are being studied clinically and preclinically. The area of drug-conjugated antibodies is progressing with encouraging data published for the trastuzumab-DM1 conjugate in a phase I clinical trial in HER2-positive breast cancer. The Dock-and-Lock platform technology has contributed to the design and the evaluation of complex antibody-cytokine and antibody-toxin conjugates. This review describes the advances made in these areas, with illustrations taken from advances made in the authors' institutions.